1994
DOI: 10.1093/jnci/86.7.499
|View full text |Cite
|
Sign up to set email alerts
|

The Bcl-2 Protein: a Prognostic Indicator Strongly Related to p53 Protein in Lymph Node-Negative Breast Cancer Patients

Abstract: The predictive role of Bcl-2 expression on 6-year relapse-free and overall survival was mainly dependent on p53 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
259
7
9

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(308 citation statements)
references
References 0 publications
33
259
7
9
Order By: Relevance
“…In our study, contrary to what was observed in other tumour types (Silvestrini et al, 1994;Krajewski et al, 1995;Apolinario et al, 1997), no relationship was found between p53 and bax or bcl-2 protein expression, i.e., cases not expressing p53 did not present any clear upregulation of bax or downregulation of bcl-2. This finding could imply that bax or bcl-2 might be regulated by mechanisms other than p53, as already reported with regard to colorectal tumours (De Angelis et al, 1998) and other tumour types including breast cancer , non-small-cell lung cancer (Apolinario et al, 1997), squamous cell carcinoma of the larynx (Fracchiolla et al, 1999) and of the oral cavity (Costa et al, 1998).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, contrary to what was observed in other tumour types (Silvestrini et al, 1994;Krajewski et al, 1995;Apolinario et al, 1997), no relationship was found between p53 and bax or bcl-2 protein expression, i.e., cases not expressing p53 did not present any clear upregulation of bax or downregulation of bcl-2. This finding could imply that bax or bcl-2 might be regulated by mechanisms other than p53, as already reported with regard to colorectal tumours (De Angelis et al, 1998) and other tumour types including breast cancer , non-small-cell lung cancer (Apolinario et al, 1997), squamous cell carcinoma of the larynx (Fracchiolla et al, 1999) and of the oral cavity (Costa et al, 1998).…”
Section: Discussioncontrasting
confidence: 99%
“…The last finding prompted us to investigate the information provided by bax, an apoptosis promoter, with that provided by bcl-2, an apoptosis suppressor. Previous reports on colorectal carcinoma established an association between bcl-2 positive staining and good prognosis (Ofner et al, 1995;Baretton et al, 1996), suggesting that bcl-2 promoted cell survival in slowly growing tumours, which was recently confirmed by Ogura et al (1999) and is in keeping with results obtained in other solid tumours (Silvestrini et al, 1994). All these studies, however, referred to patients with operable colorectal cancer submitted to surgery as the only therapeutic approach.…”
Section: Discussionmentioning
confidence: 66%
“…An important finding, with regard to the failure of Bcl-2 to predict responsiveness, seemed to be the strong negative correlation between Bcl-2 expression and p53 protein accumulation, in concordance with recent reports by other groups (Leek et al, 1994;Silvestrini et al, 1994;Joensuu et al, 1994;Gasparini et al, 1995). Recently, evidence has been obtained that wild-type as well as most mutant p53 proteins can down-regulate Bcl-2 expression in vitro and in vivo (Haldar et al, 1994;Selvakumaran et al, 1994;.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we assessed relationships between Bcl-2 expression and patient survival, response to adjuvant chemotherapy and a number of clinicopathological parameters in a series of 441 premenopausal, node-negative breast cancer patients. Bcl-2 has been reported to be frequently expressed in breast cancer and to be associated with favourable clinicopathological parameters and favourable prognosis in node-negative and node-positive breast cancers (Silvestrini et al, 1994;Joensuu et al, 1994). In women with node-positive breast cancer, Bcl-2 positivity was associated with favourable outcome in patients treated with adjuvant chemotherapy and/ or hormone therapy (Gasparini et al, 1995;Gee et al, 1994;Hellemans et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, high levels of Bcl-2 are also associated with delayed tumor progression, especially in breast cancer. Bcl-2 overexpression was found to Bcl-2 activates ATM in MCF-7 cells J Zhang et al associate with slower proliferation, high histological grade of differentiation, smaller tumor size and earlier stages of breast cancer development (Gee et al, 1994;Joensuu et al, 1994;Silvestrini et al, 1994;Daidone et al, 1999;Le et al, 1999). In several independent studies performed between 1995 and 2003, out of more than 1000 patients with stage I breast cancer who had been subjected to local-regional treatment, patients with Bcl-2-positive tumors were associated with lower relapse rates and increased overall survival during a 4-10 years of follow-up period (Silvestrini et al, 1994;Hellemans et al, 1995;Lipponen et al, 1995;Charpin et al, 1998;Daidone et al, 1999;Jager et al, 2002).…”
Section: Discussionmentioning
confidence: 99%